The impact of antiplatelet and antithrombotic regimen after TAVI: Data from the VIenna CardioThOracic Aortic Valve RegistrY (VICTORY). (13th June 2021) - Mach, Markus; Watzal, Victoria; Cuhaj, Carina; Hasan, Waseem; Poschner, Thomas; Szalkiewicz, Philipp; Strouhal, Andreas; Adlbrecht, Christopher; Delle‐Karth, Georg; Grabenwöger, Martin; Winkler, Bernhard
Abstract: Background: We compared the outcomes and adverse events of TAVI patients based on the discharge and long‐term antiplatelet or anticoagulant treatment regimens (single antiplatelet [SAPT] vs. dual antiplatelet [DAPT] vs. anticoagulation [OAC] vs. no treatment [NT]). Methods: The outcome of 532 consecutive patients treated with TAVI was evaluated. As the main study endpoint, the 1‐year all‐cause mortality was chosen to compare the different discharge treatment regimens and the 3‐year all‐cause mortality to compare the different long‐term treatment regimens. The secondary endpoints were adverse events as defined by the Valve Academic Research Consortium‐II. Results: One‐year survival after TAVI was highest amongst patients treated with DAPT compared to SAPT ( P < .001) and OAC ( P = .003), and patients under OAC demonstrated improved 1‐year survival over patients treated with SAPT ( P = .006). Furthermore, there was a strong trend towards improved 3‐year survival for patients in the OAC cohort treated with non–vitamin K antagonists compared to vitamin K antagonists (N‐VKAs vs. VKA; log‐rank P = .056). Conclusion: The lower all‐cause mortality for DAPT within the first year and N‐VKAs over VKA within the first 3 years warrant considerable attention in further recommendations of antithrombotic and anticoagulation regimens after TAVI.